Kejadian 1:29 Tentang Makanan Sehat Diaplikasikan Dalam Kesukaan Mengkonsumsi Sayur - Jelfika Tubu; Dr. Sih Wihartini M. Psi. (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
God gives humans food from plants that have seeds and from trees that bear fruit with seeds that are food for humans. To find out about healthy foods in the preference for consuming vegetables. In this method of writing, the writer uses qualitative and quantitative data which is supported by books from the general public or from theology, student data to make writing easier.Healthy food that God created for living things to survive, has the energy to fill the energy that has been reduced due to activities, and God also gives vegetables and fruits to be consumed so that humans have nutrition and protein in the body from the food they eat. The love of consuming vegetables will help in preventing diseases that exist in the body but the preference for eating vegetables is usually influenced by diet, culture, economic conditions and social standards so that many people do not like vegetables even though vegetables have good nutrition for body health.God gives humans food on this earth with the aim of maintaining human physical life so that God has the initiative to provide food to get strong energy and have better nutrition.